One day and one amazing morning on Orange Street - Rocklin, Joanne (Amulet Books, 2011)
The last remaining orange tree on a Southern California street brings together neighbors of all ages as they face their problems and anxieties, including the possibility that a mysterious stranger is a threat to their tree.